6=-18x

Simple and best practice solution for 6=-18x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=-18x equation:


Simplifying
6 = -18x

Solving
6 = -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
6 + 18x = -18x + 18x

Combine like terms: -18x + 18x = 0
6 + 18x = 0

Add '-6' to each side of the equation.
6 + -6 + 18x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 18x = 0 + -6
18x = 0 + -6

Combine like terms: 0 + -6 = -6
18x = -6

Divide each side by '18'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| -6(x+4)+3x+6=5x+9 | | 3x+7-10y=-4x+11-5y | | -5.7(r+10)+9=7(r-4.8)-1.6 | | 10(2x+1)-6=12(x+1)+8(x-2) | | 3+42x=28x+27 | | 55r^2+2r-8= | | s-(-12)=25 | | -6(x+4)+3x+6=fx+9 | | x^2=2x^2-81 | | -12.1y+12.7=-12.2y-9.5 | | (4x^2)+2x-1=0 | | 11=-7+p | | -m=12 | | 8y-4+14=9 | | 4x+5x-9=6+3 | | -3y+38=8(y+2) | | 3(9+6m)= | | (5x6)/2 | | 4=5sin(8x) | | -23.1t+22=-6.9t+22.5 | | 62-8-z+3=0 | | -6v+3=-3(2v+10) | | -19=-14+r | | 4n-16=24 | | 46+m=-23 | | -2(x-4)=-8-2x | | 5(3x+5)=6(x-3)-18 | | 5u-29=-4(2-3u) | | X+.09x=730 | | 7x-8=69-4x | | 5-9x=5-4x-5x | | 3x+15=63 |

Equations solver categories